Dampak negatif penggunaan smartphone secara berlebihan pada kalangan remaja serta upaya menanganinya - Komariyah, Aliyah Nur (Maliki Interdisciplinary Journal, 2025)
Information and communication technology has rapidly advanced, increasing smartphone usage among teenagers. However, excessive smartphone use can negatively impact mental and physical health, such as sleep disorders, anxiety, reduced concentration, and diminished empathy in social interactions. This study examines the negative effects of excessive smartphone usage on teenagers and strategies to address these issues using a literature review method. The research reviews scientific journals and academic articles discussing the relationship between smartphones, social media, and mental health. The findings show that smartphone addiction can trigger stress, depression, and reduce direct social interactions. Additionally, teenagers actively using social media are more vulnerable to cyberbullying and social comparisons that lower their self-confidence. To tackle these problems, preventive measures are necessary, such as limiting smartphone usage time, promoting digital literacy education, and raising awareness about the importance of balancing digital life with direct social interactions.